ASSESSMENT OF GAS-HYDROTHERMAL ACTIVITY OF THE BAIKAL RIFT IN THE LAKE AREA FROM NUMERICAL EXPERIMENT DATA - V. I. Gunin (Геодинамика и тектонофизика)
The Baikal rift is characterized by high heat flow, seismic activity and large thickness of sediments through which gas and hydrothermal water are intensely released into the lake water. In the area of the southern Baikal at the beginning of the 20th century, 'water pillars' were observed to reach almost a dozen metres height when earthquakes took place. This suggests potential uplift of significant amounts of gas from the lake's bottom into the atmosphere and confirms a relationship between seismicity and methane emissions. Moreover, strong emissions of gas take place in many regions of Lake Baikal, and when the lake is covered by ice, such phenomena can cause the occurrence of spots with melted ice wherein an effect of water 'boiling' is observed. In recent international space studies of the surface of ice covering Lake Baikal in spring periods, mysterious rings of 5 to 7 km in diameter were discovered. Causes and mechanisms of their occurrence have not been studied in detail yet. It is established that a ring-shaped structure results from an uplift of deep water which causes clock-wise vortex flows. Uplifting of deep water can accompany emissions of significant amounts of methane from sediments, activation of thermal vents or gas-water-mud volcanoes at the bottom of Lake Baikal. In order to reveal causes and conditions of the above-described phenomena, the author designed a 3D model of heat-and-mass transfer in viscous medium and used it for numerical simulations. Based on the obtained results, it is established that a ring-shaped structure is formed on ice of the lake by a toroid-shaped ascending convective flow that occurs due to horizontal and vertical gradients of density, and the central part of such a flow rotates in the counter-clockwise direction (i.e. cyclonic vortex), while its periphery parts rotate in the clockwise direction (i.e. anticyclonic vortex).  Both hydrothermal vents and gas emissions can produce such ascending flows. Spots with melted ice can be formed when the temperature of hydrothermal vents amounts to 30–50 °С; such a melted-ice spot can stay open as long as the hydrothermal vent is active. With an assumption of 100 % concentration of gas in the source, the numerical simulation shows that during gas release into the atmosphere, a gas pillar can reach a height of 15 metres if the source of gas is active for a period no shorter than the time required for the gas flow to ascend through the water layer and to release into the air above the water surface. An area, wherein gas is released in bubbles, can be formed in case of lasting activity of a gas source wherein the volume of gas varies from 1 % to 20 % (i.e. gas-water mix).